Dual-switchable surfaces between hydrophobic and superhydrophobic fabricated by the combination of click chemistry and RAFT - M. S. Han; X. Y. Zhang; L. Li; C. Peng; L. Bao; E. C. Ou; Y. Q. Xiong; W. J. Xu (eXPRESS Polymer Letters)
A dual-switchable surface between hydrophobic and superhydrophobic has been fabricated successfully by combining reversible addition-fragmentation chain transfer polymerization (RAFT) polymeric technology and thiol-NCO click chemistry. Well-defined block copolymer, poly(7-(6-(acryloyloxy) hexyloxy) coumarin)-b-poly(N-Isopropylacryl amide), was synthesized by RAFT, and then the block copolymer was grafted onto the surface of SiO2 modified by toluene disocynate (TDI) via thiol-NCO click chemistry. The results of nuclear magnetic resonance (NMR) and Fourier Transform Infrared (FTIR) spectroscopies confirmed that the block copolymer (Number average molecular weight (Mn) = 9400, polydispersity index (PDI) = 1.22) has been synthesized successfully. The static contact angle (CA) of the surface prepared by SiO2/P (7-6-AC)-b-PNIPAAm switches from 98±2 to 137±2° by adjusting the temperature. Furthermore, the contact angle can also oscillate between 137±2 and 157±2° on the irradiation of UV light at 365 and 254 nm, respectively. The dual-switchable surfaces exhibit high stability between hydrophilicity and superhydrophobicity. Therefore, the method provides a new method to fabricate the dual-stimuli-responsive surface with tunable wettability, reversible switching, and also be easily extended to other dual-responsive surfaces. This ability to control the wettability by the adjustment of the temperature and UV light has applications in a broad range of fields.